Fertilizer - Cassou, Emilie (World Bank, Washington, DC, 2018)
Over the past 50–60 years, unbridled growth in global fertilizer use to boost and maintain crop yields has polluted natural and agricultural systems, leading to a range of harmful outcomes. The abundant and inefficient application of fertilizer is a leading cause of water pollution, as well as a contributor to greenhouse gases and the deterioration of air and soil quality. This, in turn, has adverse consequences for public health, the climate, wildlife, and business—including tourism, agribusiness, commercial fishing, and farming. Although its use, in combination with other Green Revolution technologies, is credited for feeding the world and averting a more dramatic expansion of agriculture into natural landscapes, today’s fertilizer use is considered to be pushing the planet’s biogeochemical boundaries.